2016
DOI: 10.4103/1319-3767.191142
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer liver metastasis trends in the kingdom of Saudi Arabia

Abstract: Background/Aim:To elucidate colorectal cancer (CRC) disease patterns, demographics, characteristics, stage at presentation, metastases, and survival rates of patients, particularly those with liver metastases, at our center as the first report from the Kingdom of Saudi Arabia.Patients and Methods:We performed a retrospective, single-center database study based on the histological diagnosis of CRC in patients seen at the King Khalid University Hospital between 2007 and 2011.Results:427 cases of CRC with a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…With an increasing incidence rate and poor prognosis, CRC is commonly considered a devastating disease (2). By 2030, 2.2 million new cases and 1.1 million cases of mortality are predicted to occur, a situation that is responsible for the rising global burden of CRC (23). Although numerous studies have reported that unhealthy dietary habits, environmental changes and genetic aberrancies may be the primary causes of CRC, the precise molecular events orchestrating CRC initiation and progression remain elusive (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…With an increasing incidence rate and poor prognosis, CRC is commonly considered a devastating disease (2). By 2030, 2.2 million new cases and 1.1 million cases of mortality are predicted to occur, a situation that is responsible for the rising global burden of CRC (23). Although numerous studies have reported that unhealthy dietary habits, environmental changes and genetic aberrancies may be the primary causes of CRC, the precise molecular events orchestrating CRC initiation and progression remain elusive (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Saudi authors, who also marked the growing CRC incidence in the country last years, reported almost similar data on the tumor sites distribution: rectum 28.1% and sigmoid 37.7% with a negligible proportion of the ascending colon. 24 In order to get an overall idea on our current situation with CRC incidence rates, the same indices throughout other countries from different world regions were being compared. Reportedly, as of 2016 across the European high-income countries, CRC incidence rates were 38.9 in Norway and 29.2 in Sweden, whereas in Finland, where a national organized program was available, they were 23.5, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The global burden of CRC is rising, with 2.2 million new cases (and 1.1 million deaths) predicted to occur by 2030 [ 12 ]. Numerous studies showed that unhealthy dietary habits and environmental changes might be the primary causes of CRC; however, the molecular events controlling CRC development and progression remain unclear [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%